The potential of cow traction in the East African highlands - Zerbini, E.; Gebre-Wold, A.; Shapiro, Barry I. (Animal Traction Network for Eastern and Southern Africa (ATNESA), 1999)
To test the feasibility of the use of dairy cows for draft the International Livestock Research Institute (ILRI) and the Institute of Agricultural Research (IAR) in Ethiopia have studied a herd of F1 Friesien x Boran crossbred cows on-station over three years together with on-farm experiments and economic analyses. The total number of days in milk of working cows was similar to that of non-working cows. However, days in milk of working supplemented cows were 14 to 39 percent greater than non-working or working non-supplemented cows over two years. Milk yield of non-supplemented cows, whether working or not, was approximately half that of supplemented cows. Even though, over a period of two years, milk production of working cows was not significantly different from that of non-working cows, working non-supplemented cows had the lowest milk yield among all groups. This indicates that work with inadequate feeding would not be a feasible option for a production system involving the use of lactating cows for draft. On the other hand, total milk production of working supplemented cows over three years was only 10 percent lower than that of non-working supplemented cows. There was a dramatic decrease in percentage of cows showing oestrus and in conception rate when work was applied to non-supplemented cows. Once pregnancy was established there was no effect of work on maintenance of pregnancy. Over a period of two years the productivity index of supplemented cows was greater than that of non-supplemented cows (0.38 and 0.24, respectively), but it was similar between working and non-working cows (0.35 and 0.33, respectively). Work output more than compensated for the small decline in milk production and number of calvings and greater daily metabolic intake of working supplemented compared to non-working supplemented cows. The incremental benefit/cost ratio of having supplemented working cows over the traditional system of local cows and oxen is about 3.5 and the incremental internal rate of return is 78 percent.